Dual-SNOM investigations of multimode interference in plasmonic strip waveguides. Issue 20 (9th May 2017) - Klein, Angela E.; Janunts, Norik; Schmidt, Sören; Bin Hasan, Shakeeb; Etrich, Christoph; Fasold, Stefan; Kaiser, Thomas; Rockstuhl, Carsten; Pertsch, Thomas
Abstract : The Dual-SNOM technique provides a "non-invasive" method of local excitation and detection of individual photonic and plasmonic modes. Abstract : The ability of squeezing and guiding light in nanoscale plasmonic waveguides makes them especially interesting for photonic circuits. In spite of reported realizations of plasmonic waveguides, experimental studies on the content of plasmonic modes and mode-selective excitation methods are rare. We apply here a Dual-SNOM technique, incorporating two aperture scanning near-field optical microscopes, for simultaneous near-field excitation and detection of plasmonic modes in gold strip waveguides. Depending on the waveguide width, either a single waveguide mode or a beating pattern of several modes is observed. The relative excitation strengths of the individual modes in multi-mode waveguides are shown to be controllable by the lateral position of the excitation tip. The excitation coefficients are described by an analytical model and the results are fully corroborated by analytical calculations and full-wave numerical simulations. The Dual-SNOM technique provides a "non-invasive" method of local excitation and detection of photonic modes thus making it a valuable tool for in situ characterization of complex photonic micro- and nanostructures.